FIRST ORDER OUTAGE STATISTICS OF ASYMMETRICAL RF-OW DUAL-HOP RELAY COMMUNICATIONS - Panić, Stefan; Mahoncenko, Sergei; Stefanović, Časlav; Stefanović, Mihajlo (Bulletin of Natural Sciences Research, 2020)
This paper addresses the first-order outage statistics of asymmetrical radio frequency (RF)-optical wireless (OW) relay systems over non turbulent-induced-fading (nTIF) and turbulent-induced-fading (TIF) channels. We rely on dual-hop amplify-and-forward relay (AFR) scheme and provide detailed mathematical development for derivation of novel exact analytical as well as novel closed form approximative expressions for: i). cumulative distribution function, ii.) outage probability, and iii.) average bit-error-rate. The system under consideration is modeled as the product of independent Nakagmi-m and double squared Nakagami-m (also known as Gamma-Gamma) random processes. The obtained results of the proposed system are graphically presented for RF-OW TIF and nTIF channel sets of parameters. Moreover, the detailed comparisons of exact and approximated numerical results whose derivation resorts on exponential Laplace approximation method (LAM) are provided and thoroughly examined for the considered RF-OW statistical measures.